Counsels of imperfection : thinking through Catholic social teaching - Hadas, Edward (The Catholic University of America Press, 2021)
"The book is aimed especially to curious newcomers, especially people who do not want to be told that there are simple Catholic answers to the complicated problems of the modern world. The goal is not only to explain what the Church really says, but also how it got to its current position and who it is arguing with. For each topic, Counsels of Imperfection provides biblical, historical and a broad philosophical background. In the spirit of a doctrine always in development, Counsels of Imperfection points out both strong-points and imperfections in the teaching. The book is divided into 11 chapters. First comes an introduction to ever-changing modernity and the unchanging Christian understanding of human nature and society. Then come two chapters on economics, including a careful delineation of the Catholic response to socialism and capitalism. The next topic is government (Church and State, War, and democracy and related topics). Next two chapters on ecology. The last topic is the family teaching, which presents the social aspects of the Church's sexual teaching as relates to society. A brief concluding chapter looks at the teaching's changing response to the modern world, and at the ambiguous Catholic appreciation of the modern idea of progress"--